Improved food literacy among schoolchildren as an effect of a food camp intervention: Results of a controlled effectiveness trial. (1st February 2022) - Elsborg, Peter; Thorsen, Anne Vibeke; Ravn-Haren, Gitte; Bonde, Ane Høstgaard; Andersen, Sine Gulstad; Vermund, Marie Caroline; Klinker, Charlotte Demant; Stjernqvist, Nanna Wurr
Abstract: Food literacy (FL) refers to an individual's prerequisites for their engagement with food. Schoolchildren's FL has been defined in terms of five competencies: "to know"(e.g food-related knowledge), "to do" (e.g cooking skills), "to sense" (e.g. less well-explored sensory experiences), "to care" (e.g. taking care of oneself and others) and "to want" (e.g. willingness to take a stand and act). A cluster-based quasi-experimental effectiveness trial on the effects of a school-based intervention, "FOODcamp, " on FL, health literacy, and school well-being was conducted. A total of 640 school children in grades 6 and 7 (mean age = 12 years) attended this one-week camp and participated in different food-related classes and activities. Linear mixed models controlling for the nested structure of data showed small but significant effects for the following FL dimensions: "to do (E = 0.098, CI (0.035–0.161), p = 0.002), "to sense" (E = 0.152, CI (0.073–0.232), p < 0.001), and "to know" (E = 0.086, CI (0.022–0.150), p = 0.009) as well as for overall FL (E = 0.078, CI (0.034–0.122), p = 0.001). No effects were found for the dimensions "to want" or "to care". The intervention also had a small but significant effect on children's health literacy but not on school well-being. These findings demonstrate the value of FOODcamp and the positive impacts of a relatively brief intervention on children's FL.